Downstream evolution of ocean properties and associated fluxes in the Greater Agulhas Current System: Ad hoc Argo experiments and modeling - Morris, Tamaryn (Department of Oceanography, 2021)
The evolution of cyclonic eddies across the Southern Mozambique Chanel and the downstream evolution of the Agulhas Current was investigated using Argo floats, in combination with output from ocean general circulation reanalysis models. Two dedicated experiments were undertaken in April and July 2013, whereby eight floats were deployed within two separate cyclonic eddies. Floats were set to either daily and five-daily profiling from 1000 db to the surface, with park depths ranging from 300 db to 1000 db. The two cyclonic eddies propagated southwestward across the Mozambique Channel from southwest Madagascar to the KwaZulu-Natal Bight, a distance of approximately 1300 km, in approximately 130 days at a mean speed of 0.13 m s−1 . Estimates indicate the April (July) eddy showed mean trapped depths of 595 ± 294 m (914 ± 107 m), volume transport of 13.4 ± 5.2 Sv (21.2 ± 9.1 Sv), heat flux of -0.07 ± 0.06 PW (-0.2 ± 0.09 PW) and freshwater flux of 0.04 ± 0.04 Sv (0.09 ± 0.05 Sv). These results highlight the role of Madagascar cyclonic eddies as transporters of cooled and freshened source waters into the Agulhas Current. During a third experiment, six floats were deployed in the Agulhas Current, and exited the current within 9 - 12 days at mean speeds of 0.51 – 0.76 m s−1 . An evolution of properties was shown from north to south for both Argo data and model output; for volume transport (16.76 – 38.18 Sv; 17.70 – 32.51 Sv), heat fluxes (0.85 – 1.79 PW; 0.99 – 1.91 PW) and salt fluxes (0.60 – 1.37 x 1012 kg s−1 ; 0.63 – 1.17 x 1012 kg s−1 ). This study illustrates the first near-real time survey of the Agulhas Current, and a potential method of quasi-synoptic surveys using Argo float technology. These experiments highlight alternative methods of studying regions of turbulence by altering the mission parameters of Argo floats. Increased observations of eddies and Western Boundary Currents are critical to our understanding of the global oceans and impacts on the earths climate. Even more so for the understudied Indian Ocean.